JURIDICAL ANALYSIS OF SUPREME COURT DECISION NUMBER 179K/PDT.SUS-PHI/2024 REGARDING THE FULFILLMENT OF PKWTT WORKERS RIGHTS AFTER TERMINATION FOR EFFICIENCY REASONS - Nikmah, Fadhilatun; Nugroho, Arinto (Indonesian Journal of Labour Law and Industrial Relations, 2024)
The termination of employment relationship carried out by PT Synerga Tata Internasional to Muhammad Nasir on the grounds of efficiency in preventing losses resulted in a dispute between themuntil the issuance of the Supreme Court Decision Number: 179k/Pdt.Sus-PHI/2024. This layoff is carried out by injuring labor law due to the offer of layoff compensation that is not in accordance with applicable regulations. The difference between the decision of the panel of judges of the first instance stating that the lawsuit is inadmissible (niet ontcvankelijk verklaard) and the decision of the panel of judges of the cassation level stating that the Plaintiff's lawsuit was partially granted resulted in a significant difference in how the judge viewed, considered, and provided the basis for the decision on the settlement of the dispute that occurred. This study aims to examine the basis of legal considerations (ratio decidendi) used by the Panel of Judges in deciding disputes and understanding the appropriate case resolution in deciding disputes. The type of research used in this study is normative legal research or doctrinal hukm research which is carried out through literature review or secondary data. The results of this study show that the Plaintiff's lawsuit cannot be said to be formal and premature smallpox, so it cannot be declared that the lawsuit is inadmissible. Beside it,, based on Article 43 paragraph (2) of PP 35/2021, the Plaintiff is entitled to Severance Pay, Service Period Award Money, and Compensation Money as compensation received as a result of the layoffs experienced.